Social acceptance of small modular reactor (SMR): Evidence from a contingent valuation study in South Korea - Eunjung Cho; Juyong Lee (Nuclear Engineering and Technology)
This study provides a comprehensive analysis of the social acceptance of the Small Modular Reactor (SMR) in South Korea. The growing interest in SMRs as a potential solution to the challenges of climate change and energy security highlights the need for continued research and development in this area. The research was conducted using a contingent valuation method, which involved surveying a representative sample of the South Korean population. Out of a total of 1032 respondents, 78 % were willing to pay for SMR development. The mean WTP was estimated to be USD 4.28 per year per household and scaled up to the national level in South Korea, it was analysed to have a total economic and social benefit of USD 0.49 billion. The more serious the respondents perceived the current and future problem of climate change to be, the more likely they were to be willing to pay an offered bid amount. This study suggests that the need to address climate change and the need to raise awareness of SMR as one of the low-carbon technologies at the government level is required to generate the appropriate level of social acceptance to promote SMR development.